Periacetabular Osteotomy for Developmental Dysplasia of the Hip and Femoroacetabular Impingement: A Study Using the U.K. Non-Arthroplasty Hip Registry (NAHR) Data Set. (5th August 2020) - Holleyman, Richard; Sohatee, Mark Andrew; Witt, Johan; Bankes, Marcus J.K.; Andrade, Tony J.; Board, Tim; Lee Conroy, Jonathan; Wilson, Matthew; McBryde, Callum; Khanduja, Vikas; Malviya, Ajay
Abstract : Background: Periacetabular osteotomy (PAO) is a well-recognized procedure for the treatment of hip dysplasia in young adults and can be used for the surgical management of femoroacetabular impingement (FAI) with acetabular retroversion. The aim of this study was to use a national database to assess the outcomes of PAO for developmental dysplasia of the hip (DDH) and for FAI. Methods: All patients in whom an isolated PAO had been performed between January 2012 and February 2019 were identified in the Non-Arthroplasty Hip Registry (NAHR). Their outcomes were assessed using the EuroQol-5 Dimensions (EQ-5D) index and the International Hip Outcome Tool (iHOT)-12 preoperatively and then at 6 months, 12 months, and 2 years postoperatively. Results: Six hundred and thirty (630) PAOs were identified, with 558 (89%) performed for DDH and 72 (11%) performed for FAI. Most patients (90%) were female. The mean age in the DDH group (31.2 years) was significantly higher (p < 0.0001) than that in the FAI group (26.5 years). There were no other significant between-group demographic differences. Preoperatively and at each follow-up time-period, iHOT-12 scores were better in the DDH group than in the FAI group; however, only the preoperative scores differed significantly. There was significant improvement between the preoperative and 6-month iHOT-12 and EQ-5D index scores in both the DDH and the FAI group. This improvement was maintained at 12 months postoperatively, by which time almost 90% of the patients had achieved the minimum clinically important difference (MCID) in their iHOT-12 score. Conclusions: This study shows that PAO is a successful surgical intervention for DDH and FAI in the short term, with significant improvement in patient-reported outcome scores that is maintained up to 2 years postoperatively. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.